Preparedness for Candida auris in Canadian Nosocomial Infection Surveillance Program (CNISP) hospitals, 2018. (13th March 2020) - Garcia-Jeldes, Felipe; Mitchell, Robyn; Bharat, Amrita; McGeer, Allison
Abstract: We surveyed Canadian Nosocomial Infection Surveillance Program hospitals to evaluate infection prevention and microbiology laboratory preparedness for Candida auris . We identified significant gaps: most hospitals were not prepared to screen patients for colonization, and only one-half of laboratories reported identifying all clinically significant Candida isolates to the species level.